Application of modified least squares method for order reduction of commensurate higher order fractional systems - Kalyana Kiran Kumar; Chongala Prasad; S Ramanjaneyulu Korada; B. Srinivasa Rao (IAES Indonesian Section, 2020)
The paper related to the reduction and investigation of family of commensurate fractional order systems. The fractional order system is first transformed to integer order and then a hybrid method is applied as a model reduction scheme. In this scheme the reduced denominator is acquired by least square method and the numerator is achieved by time moment matching. This formulated reduced integer model is reconverted to reduced fractional model. Three examples are conferred to authenticate and emphasize the efficacy of the proposed approach. The proposed method is verified by MATLAB simulation, and shows better performance in the estimation process.